Strategic competence of students in solving linear program problems based on mathematical anxiety - M. Fauzan Asy'ari; Tatag Yuli Eko Siswono; Agung Lukito (STKIP PGRI Banjarmasin, 2020)
This descriptive qualitative research aims to describe the students' strategic competence with high and low mathematical anxiety in solving linear program problems. The subjects of this research were one student with low mathematical anxiety (S1) and one student with high mathematical anxiety (S2). The main instrument was the researchers supported by the test instrument and interview guidelines. Data from test and interview results were analyzed using steps data reduction, data display, and conclusion drawing. The results showed that both participants formulated problems by writing down the essential information and linking pieces of information with prior knowledge. Both participants represented problems by using words in formulating problems. S1 described problems using mathematical models, equations, graphs, and concepts in solving problems while represented problems using tables, mathematical models, equations, charts, and concepts in solving problems. Both participants resolved problems by planning a solution and implementing it. S1 determined and choose the correct answer of the problems while S2 had difficulty in modeling problems so that S2 modeled problems by guessing. S2 was wrong in modeling problems. Finally, the next work steps of S2 were also wrong, and S2 did not find the correct solution.